Bioprinting of human nasoseptal chondrocytes‐laden collagen hydrogel for cartilage tissue engineering. Issue 3 (17th February 2021) - Lan, Xiaoyi; Liang, Yan; Erkut, Esra J. N.; Kunze, Melanie; Mulet‐Sierra, Aillette; Gong, Tianxing; Osswald, Martin; Ansari, Khalid; Seikaly, Hadi; Boluk, Yaman; Adesida, Adetola B.
Abstract: Skin cancer patients often have tumorigenic lesions on their noses. Surgical resection of the lesions often results in nasal cartilage removal. Cartilage grafts taken from other anatomical sites are used for the surgical reconstruction of the nasal cartilage, but donor‐site morbidity is a common problem. Autologous tissue‐engineered nasal cartilage grafts can mitigate the problem, but commercially available scaffolds define the shape and sizes of the engineered grafts during tissue fabrication. Moreover, the engineered grafts suffer from the inhomogeneous distribution of the functional matrix of cartilage. Advances in 3D bioprinting technology offer the opportunity to engineer cartilages with customizable dimensions and anatomically shaped configurations without the inhomogeneous distribution of cartilage matrix. Here, we report the fidelity of  F reeform  R eversible  E mbedding of  S uspended  H ydrogel (FRESH) bioprinting as a strategy to generate customizable and homogenously distributed functional cartilage matrix engineered nasal cartilage. Using FRESH and in vitro chondrogenesis, we have fabricated tissue‐engineered nasal cartilage from combining bovine type I collagen hydrogel and human nasoseptal chondrocytes. The engineered nasal cartilage constructs displayed molecular, biochemical and histological characteristics akin to native human nasal cartilage.